2015
DOI: 10.1007/s00404-015-3849-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose isoflavone aglycone alleviates psychological symptoms of menopause in Japanese women: a randomized, double-blind, placebo-controlled study

Abstract: PurposeMany studies have demonstrated the effectiveness of isoflavones on menopausal symptoms; however, these mostly used high dosages. Because high-dose isoflavone may result in endometrial hyperplasia, we investigated whether low-dose isoflavone aglycone alleviates menopausal symptoms similarly to high dosages.MethodsWe conducted a randomized, double-blind, placebo-controlled study in 90 healthy women aged 40–60 years who had at least one menopausal symptom on the Menopausal Symptom Scale (MSS). The particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 41 publications
(39 reference statements)
0
70
0
5
Order By: Relevance
“…94 In contrast to the benefit of this dose, this eight-week trial found that a very low dose of isoflavones (12.5 mg/d) lacked efficacy. It is noteworthy that isoflavone exposure occurred via treatment and as a result of a likely background dietary intake of about 40 mg/d.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…94 In contrast to the benefit of this dose, this eight-week trial found that a very low dose of isoflavones (12.5 mg/d) lacked efficacy. It is noteworthy that isoflavone exposure occurred via treatment and as a result of a likely background dietary intake of about 40 mg/d.…”
Section: Introductionmentioning
confidence: 81%
“…Of the 20 trials in Table 1 that evaluated the mood and anti-depressant effects of isoflavones (or an isoflavone metabolite), nine found evidence of efficacy, 94,98,100-102,104,109,110,112 and a tenth found benefit at one dose but not another. 97 In addition to these ten trials the findings from one other trial are suggestive of benefit when considering the relatively low intervention dose and short study duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, over a two-year period, an Italian study that was evaluating mood effects, found that postmenopausal women taking 54 mg/day genistein showed a decline in depressive symptoms as measured by the Zung Self-rating Depression Scale whereas no change occurred in the placebo group [330]. Also, a Japanese study involving peri- and postmenopausal women found that a very moderate dose (25 mg/day) of isoflavones consumed in aglycone form reduced depressive symptoms as assessed by the Hospital Anxiety and Depression Scale and also reduced anxiety as assessed by the Athens Insomnia Scale [331]. In contrast to the benefit of this dose, this eight-week trial found that a very low dose of isoflavones (12.5 mg/day) lacked efficacy.…”
Section: Mental Healthmentioning
confidence: 99%
“…A daidzein metabolizmusának lépései [20] ÖSSZEFOGLALÓ KÖZLEMÉNY Az izoflavonoidok 25 mg dózisban már szignifikánsan csökkentették a depressziós tüneteket és az alvászavart is, emellett a Menopauza Skála értékeiben is szignifikáns javulást regisztráltak [24].…”
Section: áBraunclassified